Subconjunto terminológico da CIPE® para lactentes com alergia à proteína do leite de vaca - Martins, Tatiane Graça (2016)
Introduction: The increasing number of children with food allergy in recent years, has become a serious public health problem in Brazil and in the world. Like this, children with food allergy, highlighting the allergy to cow's milk protein (APLV) need quality nursing care, based on a systematized query. For such the International Classification for Nursing Practice (CIPE®) is an effective methodological tool that assists the nurse's clinical practice and elaboration of a terminological subset of CIPE® contributes to safe and knowable care planning. Objective: To elaborate a CIPE® Terminology Subset for infants with cow's milk protein allergy. Method: Methodological research subsidized by Horta's Human Needs Theory (NHB) and Human and Social Needs organized by Garcia and Cubas. Developed in four stages: Identification of the empirical indicators and relevant terms of the CIPE® for infants diagnosed or suspected of having APLV; Cross-mapping of the terms identified in the empirical indicators with the terms of the CIPE®; Elaboration of Diagnostic statements/Nursing Outcomes and Interventions; Composition of the Terminological Subset for infants with APLV. The sample consisted of 20 children from zero to two years, attended at the Food Allergy Center of Sergipe Results: The 48 empirical indicators, resulting from the form applied to those responsible for the sample, were distributed in 14 human needs, organized in the group of psychobiological needs Psychosocial needs and psychospiritual needs. These were validated by nurses-Judges and resulted in the instrument of data collection for the nursing consultation, As well as in the bank of terms that subsidized the elaboration of the Terminological Subset for Infants with APLV, composed of 137 diagnoses/results and 126 nursing actions. Conclusion: The CIPE® Terminology Subset for infants with APLV proposes to be a facilitating tool for the nursing consultation of this clientele and a universal documentation so that all nurses can use and contribute to its improvement.